2018
DOI: 10.1145/3274342
|View full text |Cite
|
Sign up to set email alerts
|

Debiasing Desire

Abstract: Designing technical systems to be resistant to bias and discrimination represents vital new terrain for researchers, policymakers, and the anti-discrimination project more broadly. We consider bias and discrimination in the context of popular online dating and hookup platforms in the United States, which we call intimate platforms. Drawing on work in social-justice-oriented and Queer HCI, we review design features of popular intimate platforms and their potential role in exacerbating or mitigating interpersona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…We follow up on Birnholtz et al (2014), who found that Grindr users use specific language in their profiles to manage reactions and stigma from others, to investigate users' reasonings and strategies. In alignment with Hutson et al (2018) who "argue that focusing on platform design can reveal opportunities to reshape troubling patterns of intimate contact without overriding users' decisional autonomy", we further explore the socio-cultural impacts of design-based features (pg. 1).…”
Section: Designing For Multivalent Intimate Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…We follow up on Birnholtz et al (2014), who found that Grindr users use specific language in their profiles to manage reactions and stigma from others, to investigate users' reasonings and strategies. In alignment with Hutson et al (2018) who "argue that focusing on platform design can reveal opportunities to reshape troubling patterns of intimate contact without overriding users' decisional autonomy", we further explore the socio-cultural impacts of design-based features (pg. 1).…”
Section: Designing For Multivalent Intimate Interestsmentioning
confidence: 99%
“…In particular, we examine how current Grindr and Scruff users interact with 1) search, sort, and filter features in relation to discrimination (Hutson et al's, 2018), 2) reporting and blocking moderation features (Mowlabocus, 2020), and 3) relaxed sexual imagery on Grindr and Scruff that allows users to share content that had been previously prohibited. Through qualitative interviews and design probes, we also employ speculative design methods to explore how queer mens' experiences might change if these features worked in different ways, thus co-creating alternative ways of connecting with others on these platforms.…”
Section: Designing For Multivalent Intimate Interestsmentioning
confidence: 99%
“…I am not making the empirical claim that people will form associations with those who are unlike them, to the degree that there is no residual inequality that can be 44 Pariser 2012 45 https://developers.google.com/machinelearning/recommendation/overview/candidate-generation 46 But see Bedi 2015 for the argument that justice requires such interference, as intimacy is a primary good. Also see Hutson et al 2018 for the argument that we should "debias desire" by designing platforms in ways that make it difficult to racially discriminate in the sexual realm. attributed to sorting.…”
Section: Resolving the Problem Of Sortingmentioning
confidence: 99%
“…46 But see Bedi (2015) for the argument that justice requires such interference, as intimacy is a primary good. Also see Hutson et al (2018) for the argument that we should "debias desire" by designing platforms in ways that make it difficult to racially discriminate in the sexual realm. 47 I retain the term "intimate association" to track others' usage in the literature, but want to note I do not subscribe to it either as a category that usefully marks out a special kind of association, or as one that the state should have reason to use.…”
Section: | R E Solv I Ng T H E Probl E M Of Sortingmentioning
confidence: 99%
“…The shaping of selves, families, neighborhoods, and communities by intimate affiliations and the structures that manage them has been emphasized, underscoring the pervasive influence of intimacy on various social domains (Hutson et al, 2018). The interplay between structure and agency in the contexts of intimacy, family, and E-ISSN: 3041-8550 contemporary close relationships has been analyzed, highlighting the complex dynamics at play within intimate relationships (Ketokivi, 2012).…”
Section: Introductionmentioning
confidence: 99%